Pengentasan Rumah Tangga Rawan Pangan dan Gizi: Besaran, Penyebab, Dampak, dan Kebijakan - Agung Hendriadi; Mewa Ariani (Forum penelitian Agro Ekonomi, 2020)
One of the next development agendas is quality human capital improvement. However, the progress is affected by proportion of food insecure households not insignificantly improving. It is similar to prevalence of stunted under-five-year-old children as high as 27.9%. This paper is a critical review aiming to analyze magnitude, determinant, impact and policy alternative related with food and nutrition insecurity alleviation. Food and nutrition insecurity could be seen from perspectives of areas (island/district/city), households and individuals. Currently, there are five indicators used by the government to calculate food insecurity including three global indicators and 2 country indicators resulting in different proportion of households with food and nutrition security. There are various interlinked determinants consisting of purchasing power, sociocultural aspects, infrastructure, and natural resources. Therefore, efforts to reduce these problems should be comprehensive, sustainable and consistent in planning and implementation. Policy on self-sufficiency should be developed on the specific regions based on local resources and culture. The policy should be implemented through community empowerment especially among the poor for improving income and basic infrastructure in insecure areas. To achieve the goals, there should be collaboration between governments and representatives at central and local levels, as well as individuals.